(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
A simple and rapid method has been developed for determination of iodate in aqueous samples. The method is based on their amplification reaction with iodide in the presence of 0,1 M H3PO4 and following oxidation of methylene blue (MB). The nature of the anions of mineral acids has actually no effect on absorption of triiodide complexes. The advantage of using orthophosphate acid compared to other mineral acids in this case is that the orthophosphate-ion capable to complexing with Fe(III), and consequently his masking and preventing the oxidation iodide to iodine. The reaction can be monitored spectrophotometrically by measuring the decrise absorbance at 665 nm of methylene blue. The effect of interfering anions on determination of iodate in aqueous samples like Cl-, SO42-, NO3-, Br-, PO43-, HCO3-, C2O42-, BrO3- was studied. The tolerance ratio [Cl-]/[IO3-] was 400. Optimized parameters for the method are 8.4.10-6 М KI (1.10-2 M), H3PO4 (0,1 M), MB (8.4.10-6) М. The equation of the calibration plot calculated in the range of 1 to 7 µg iodine in a final volume of 10,0 ml is ΔA=A0-Ax=0,75∙С, µg, where A0 – optical density in the absence of iodate, Ax – optical density in the presence of iodate. In volumetric flask (10.0 cm3) was transfered 1.0 cm3 of a solution of table salt containing 1-6 µg of iodine in form of Iodate. Then in each flask was added 1.0 cm3 of 0.1 M solution of potassium iodide, 1.0 M orthophosphate acid and 8.4.10-6 M MB. The contents of the flask was mixed and after 3 min was measured the optical density (Ax) of the obtained solution at 655 nm relative to water. The iodine content in table salt samples is calculated by calibration plot. The results obtained by the present method are in good agreement with those obtained by convential iodometry.